Low Complexity Implementation of Symbol-level Precoding in Multi-user MISO System - Lee, Jaewon; Kang, Chung G. (IEEE Consumer Communications and Networking Conference, 2023)
In this paper, we consider the minimum mean square error-based constructive interference optimization (MMSE-CIO) problems to ensure the minimum required constructive interference gain under a fixed total-power constraint, which involves critical implementation issues regarding the computational complexity. The optimum solution is derived in a closed form for a digital precoder subject to a fixed analog beam, serving as a key implementation block to reduce the computational complexity in the proposed hybrid beamforming under a more complexity situation in which the different types of modulation schemes are mixed. We also show that MMSE-CIO can achieve a significant performance gain with the advantages of link adaptation over legacy CIO scheme in nonhomogeneous scenario.